2012
DOI: 10.1080/02678292.2012.669501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,3,4-oxadiazoles with different rigid cores on the thermal and electro-optical performances of liquid crystalline blue phases

Abstract: 2012) Effects of 1,3,4-oxadiazoles with different rigid cores on the thermal and electro-optical performances of liquid crystalline blue phases, Liquid Crystals, 39:5, 629-638, A series of symmetrically 2,5-disubstituted 1,3,4-oxadiazoles with different rigid cores were synthesised under the microwave irradiation based on green chemistry and atom economy. The induced blue phase (BP) behaviours of these bent-shaped compounds were investigated after blending them with a high twisted power chiral dopant or doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…It has been experimentally and theoretically confirmed that the BP II and BP I exhibit simple cubic and body-centered cubic nanostructures (Figure 8(a)), respectively. Due to the unique 3D structures of BPLCs, they exhibit many revolutionary features such as optically isotropic and alignment-layer-free, while possess superior electrooptic properties and non-linear optical responses comparable to nematics [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. Furthermore, because of the tightly wound spatial arrangement of the crystalline axis, the scattering loss due to thermal fluctuations of the director axis is considerably smaller than nematics, allowing longer interaction length and higher process efficiency.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 98%
“…It has been experimentally and theoretically confirmed that the BP II and BP I exhibit simple cubic and body-centered cubic nanostructures (Figure 8(a)), respectively. Due to the unique 3D structures of BPLCs, they exhibit many revolutionary features such as optically isotropic and alignment-layer-free, while possess superior electrooptic properties and non-linear optical responses comparable to nematics [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. Furthermore, because of the tightly wound spatial arrangement of the crystalline axis, the scattering loss due to thermal fluctuations of the director axis is considerably smaller than nematics, allowing longer interaction length and higher process efficiency.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 98%
“…To stabilize BPs over a wide temperature range, various promising strategies have been proposed including new molecular design, polymer stabilization, doping functional nanoparticles, etc. [297][298][299][300][301][302][303][304][305][306][307][308][309][310][311][312][313][314][315][316] Among them, polymer stabilization enables the formation of BPs with a wide temperature range over 60 K down to room temperature, which are very attractive for next-generation ultrafast display due to numerous advantageous properties such as sub-millisecond response time and wide viewing angle. [317][318][319][320] Interestingly, BPs have been widely investigated for photonic applications in areas of lenses, gratings, lasers, spatial phase modulators, and so on.…”
Section: Blue Phase Liquid Crystalsmentioning
confidence: 99%
“…[9][10][11] Additionally, it has been theoretically predicted that the bent-shape compounds with biaxiality may play an important role in stabilising the blue phase (BP) due to the molecular biaxiality relieving some of the frustration of the defect lines. [12] In order to design LC materials exhibiting the desired mesophase behaviour and excellent performance in fast light modulators or tunable photonic crystals, many bent-shape compounds such as 1,3-disubstituted benzene, [13] 1,2-disubstituted benzene, [14] 2,5-disubstituted 1,3,4-oxadiazole [15,16] and 2,7-disubstituted naphthalene [17] have been previously investigated by either blending them with chiral dopants or doping them into the chiral nematic liquid crystal (N*LC). Up to now, at least seven phases of banana-shape LCs have been described and these phases are not comparable with smectic phases formed by calamitic mesogens.…”
Section: Introductionmentioning
confidence: 99%